Unusual radiographic images of radiopaque contrast media incidentally observed in intracranial region: two case reports - Özlem Üçok; Umut Pamukçu; Berrin Çeli̇k; İlkay Peker (Istanbul University, 2018)
DOI: 10.26650/eor.2018.532The oil-based contrast medium has extremely slow clearance rate from cerebrospinal fluid. The medium known as myodil or pantopaque or iopenydylate was firstly introduced in 1944 to be used in myelography, cisternography and ventriculography. It was commonly used until 1980s but was later replaced by water-soluble mediums in 1990s because of its complication and sequelae. Although rare, images of the remnants may still be encountered on radiograms since its remnants may be seen after six decades. In this article, incidental radiopaque images in panoramic radiography and cone-beam computed tomography (CBCT) were presented in two patients whose myelography was taken before herniated discs' operation. Unusual incidental radiopacities in intracranial region were observed on panoramic radiography image of a male and CBCT image of a female, both of whom underwent myelography more than 30 years ago. Dentomaxillofacial radiologists should be aware of this radiographic appearance, should be able to differentiate it from possible pathologies.